Incorporation of different curcumin nanostructures in a model food: evaluation of shelf-life and behaviour under digestion - Gonçalves, Raquel Filipa Silva (2020)
Introduction. Curcumin is a lipophilic polyphenol compound widely known by its broad range of health-promoting activities. However, its application in food products is hindered by its poor solubility, quick degradation on aqueous solution and low bioavailability. One of the strategies to overcome these drawbacks is the encapsulation of curcumin on lipid-based nanostructures, improving its stability and bioavailability upon digestion. Methodology. Curcumin was encapsulated in different lipid-based nanostructures: nanoemulsions (NE), solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC). These curcumin nanostructures have been incorporated in a model food (a beverage with pH 3, composed of sucrose, citric acid, ascorbic acid and sodium benzoate) and their shelf-life and behaviour under digestion was evaluated. Samples and controls (beverage without curcumin and with free curcumin) were stored for 22 days (i.e. beverages shelf-life) at room temperature and characterized over shelf-life in terms of size, zeta-potential, colour and pH. Beverage incorporating NLC and SLN were also subject to an in vitro digestion and curcumins bioaccessibility and stability was determined. Results. Samples and controls showed a decrease of pH over time. Beverage with NLC showed the lowest increase of particles size (from 148.0 to 157.2 nm), while beverage with NE showed size instability from day 1. Also, beverages colour supported the results observed in particles size: NLC presented values of total colour difference (TCD) similar to the controls (TCD = 1.68), showing colour stability over time. During digestion, beverages with NLC and SLN were stable until the intestine phase, where an increase of particles size occurred. Beverages with nanostructures showed higher curcumins bioaccessibility and stability than the beverage with free curcumin. Also, it was possible to observe that beverage with SLN presented values slightly higher for curcumins bioaccessibility and stability than beverage with NLC. Conclusion. Beverage with NLC was found to be the most stable system throughout shelf-life. Curcumins bioaccessibility and stability during digestion varied in the following order: beverage with free curcumin, beverage with NLC, beverage with SLN. Also, it was possible to conclude that nanostructures incorporated in the beverage are more stable than nanostructures solutions.